Millimeter-range Induced Flexo-Pyrophotronic Effect in Centrosymmetric Heterojunction for Ultrafast Night-Photomonitoring - Kumar, Mohit; Seo, Hyungtak (Advanced Functional Materials, 2023)
Unlike the structure-specific piezoelectric effect, flexoelectricity is a universal phenomenon that can offer a wide range of energy-efficient, cost-effective, mechano-opto-electro-coupled applications. Even though the flexoelectric effect has been extensively studied at nanoscale, a fundamental, yet unresolved, the issue is how it can be exploited at larger scales for potential applications. Herein, the long-range (>millimeter) stimulated and regulated impact of the localized inhomogeneous strain-induced flexoelectric potential on centrosymmetric metal/titanium oxide heterojunction with nanoscale precision (≈5.8 nm) is demonstrated. The noticed phenomenon is attributed to the long-range interaction between flexoelectric and build-in potentials, which is further utilized to develop mechanically regulated (enhancement > 104%), self-powered (i.e., 0 V), ultrafast (>10 million bits per second), and broadband (λ = 365–1720 nm) pyro-photosensors having high responsivity (≈1.18 mA W−1). As prospective applications, proof-of-concept ultrafast night movement monitors (>720 km h−1), high-performing stationery, and dynamic obstacle sensors with possible impact alerts are developed. These findings lay the groundwork for the micro-to-millimeter-range flexo-opto-electrical coupling in centrosymmetric materials, which can have a wide variety of practical applications.
Keywords: Centrosymmetric; Flexoelectric; Flexoelectric effects; Long range interactions; Longer-range interaction; Millimeter range; Movement monitoring; Night-photomonitoring; Ultra-fast; Ultrafast night movement monitoring; flexoelectric effects; long-range interaction; night-photomonitoring; photodetectors; ultrafast night movement monitoring